Development of metal/ metal oxide electrocatalysts for expediting renewable hydrogen generation - Sui, Nicole L. D. (2023)
The world’s dependence on limited fossil fuel supply to meet increasing energy demands has led to its fast depletion as well as the release of copious amounts of harmful pollutants as by-products. Fortunately, cleaner renewable sources of energy are emerging as replacements for fossil fuels. One popular alternative to fossil fuels includes hydrogen fuels which are commonly generated as a product of the water-splitting process. Water-splitting involves the separation of water through two concurrent sluggish half-reactions, hydrogen evolution reaction and oxygen evolution reaction. The efficiency of these two half-reactions is limited by their large initial energy barrier which is required to activate the reaction. Thus, electrocatalysts are imperative as they can reduce the initial energy barrier, which accelerates the kinetics of the reactions. This study reports a two-step fast and facile method to synthesize metal/metal oxide aerogels for electrocatalytic water splitting in an alkaline environment. Metal aerogels were first created through a sol-gel technique with sodium borohydride as a reducing agent, which when hydrolyzed, serves as a gas template to form a porous nanoarchitecture. These pore-dense architectures in the synthesized aerogels are beneficial for the final calcination step to convert a portion of the metal to metal oxide. Notably, electrochemical tests reveal excellent electrocatalytic performance, whereby the metal/ metal oxide exhibit small overpotentials at 10 mA cm-2 of 34 mV for the hydrogen evolution reaction and 189 mV for the oxygen evolution reaction, which is lower than 53 mV and 338 mV for the Pt/C and RuO2 benchmarks, respectively. Specifically, the great electrocatalytic activity of the metal/ metal oxide aerogels can be attributed to its high pore density, in concert with its metal/ metal oxide heterointerface, and tensile strain. These combined benefits can maximize active site exposure, expedite carrier migration, and optimize reaction intermediate binding energies in electrocatalytic water-splitting. Particularly, certain aspects of electrocatalytic research could be improved with the aid of 3D printing. For instance, 3D printing could potentially aid the fine control of the bulk shape and size of the electrocatalyst through extrusion and deposition techniques. 3D printing can also actualize optimized designs of electrodes and apparatus used for electrochemical testing. Therefore, 3D printing could be the key to solving many major structural problems in the developmental journey of future electrocatalysts.